ORAL BACTERIA AND SYSTEMS DISEASES: A REVIEW - Moromi Nakata, Hilda (2004)
In order to show a global vision of oral bacteria in systemic diseases, it is important to analyze the presence and consequences of these microorganisms in relation with: bacteremia, endocarditis, cardiovascular disease, cerebrovascular disease, bacterial pneumonia, neonatal weight, nefritis, arthritis, dermatitis and diabetes mellitus, reaching conclusions for each one of them.